1995
DOI: 10.1128/jvi.69.8.4957-4962.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cross-protection of mice against a global spectrum of rabies virus variants

Abstract: Rabies, a continuing worldwide problem, kills tens of thousands of people and millions of animals each year.The problem is most severe in developing countries, where cell culture-derived vaccines are unaffordable and the available nervous tissue-derived vaccines are often of questionable immunogenicity and may produce neurological complications. To determine the feasibility of developing a vaccine with worldwide applicability, we investigated whether recombinant vaccinia viruses expressing either the glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Importantly, VBRV and most other bat-associated rabies viruses are maintained in species-specific transmission cycles without alternative hosts that could otherwise compromise vaccination campaigns 37,60 . Moreover, rabies vaccines are broadly protective across Rabies lyssavirus strains and even protect against other lyssaviruses, suggesting that viral antigenic evolution would not be a relevant barrier 61,62 . Finally, decades of experience in vampire bat population control have equipped most Latin American countries with the operational capacity to implement vaccination campaigns alongside or in lieu of culling efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, VBRV and most other bat-associated rabies viruses are maintained in species-specific transmission cycles without alternative hosts that could otherwise compromise vaccination campaigns 37,60 . Moreover, rabies vaccines are broadly protective across Rabies lyssavirus strains and even protect against other lyssaviruses, suggesting that viral antigenic evolution would not be a relevant barrier 61,62 . Finally, decades of experience in vampire bat population control have equipped most Latin American countries with the operational capacity to implement vaccination campaigns alongside or in lieu of culling efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This vaccine strain had 97% protein sequence similarity to the nucleoprotein of Nepalese viruses in both the Arctic-like and Indian subcontinent clades, whilst the glycoprotein from the vaccine strain had 91–92% similarity to these Nepalese viruses. However cross-protection of isolates belonging to the species RABV in the genus Lyssavirus is quite broad and studies have shown vaccine candidates to elicit protective immunity to many varied rabies strains [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently available vaccines mostly belong to GT1, against which they give protection (23). However, the protection against GT4 to GT6 depends on the vaccine strain.…”
mentioning
confidence: 99%